Composition and properties of drilling and completion fluids - Caenn, Ryen (Gulf Professional Pub., 2011)
The petroleum industry in general has been dominated by engineers and production specialists. The upstream segment of the industry is dominated by drilling/completion engineers. This text incorporates information on technology, economic, and political issues that have impacted the use of fluids to drill and complete oil and gas wells.